Production of Planting Material of Selected Sweet Potato (Ipomoea batatas [L.] Lam.) Clones under Different Multiplication Methods - Bahati Abdallah; Hemedi Mkuzi Saha; Stephen Mwangi Githiri; Wariara Kariuki (Research Advances and Challenges in Agricultural Sciences Vol. 7, 2024)
Sweet potato is a staple food that contributes to food security for communities in Sub-Saharan Africa. Its storage roots are rich in energy, proteins, vitamins and other important micronutrients. The crop is among the traditional food crops grown in Kenya. Production of sweet potato in coastal Kenya is low and this has been associated with scarcity of planting material at the onset of rains. A study was therefore conducted at the Pwani University farm to evaluate different methods for the production of sweet potato planting material. The methods (treatments) evaluated in this study were: Planting in pits without lining, planting in pits with lining, planting on flat ground, planting in sacks without lining and planting in sacks with lining. A Randomized Complete Block Design was used, with factorial arrangement of treatments which were replicated three times. Vine yield data was collected from the experimental plots and subjected to the analysis of variance using the General Linear Model. In the long rains season, sweet potato in the treatments without lining produced longer vines than those in the treatments with lining. Different vine planting methods produced similar vine lengths in the off-season multiplication under irrigation. The planting methods without lining are recommended for use by farmers during the long rains season multiplication of planting material. It is also recommended that farmers start the multiplication during off-season and continue up to the beginning of the long rains season, so as to obtain enough planting material at the onset of the planting season for sweet potato. This will also lead to the production of excess planting material which may be used to expand the area under sweet potato.